(untitled) (Bangladesh Agronomy Journal, 2018)
A site-specific nutrient management (SSNM) field trial was conducted for irrigated rice using five fertilizer treatments: i) omission of N, ii) omission of P, iii) omission of K, iv) NPK and v) farmers’ practice (FP). Substantial variation in the native N, P, and K supply was found among farmers’ fields. The indigenous soil K produced 4.5 to 5.0 t ha-1 but native P and N gave only rice yield of 3.5 to 4.0 t ha-1. The highest grain yield (6.0 to 7.5 t ha-1) was obtained from balanced fertilization, followed by FP (4.0 to 5.0 t ha-1).The optimal grain yield at Faridpur was obtained by using N, P and K at 135, 8 and 49 kg ha-1; 139, 9 and 42 kg ha-1; and 140, 10 and 43 kg ha-1 for high, medium and low land rice, respectively. However, for Gopalgonj district fertilizer doses of N, P and K were 140, 11 and 38 kg ha-1; 142, 10 and 42 kg ha-1; and 138, 10 and 49 kg ha-1; and for Madaripur district, 126, 8 and 46 kg ha-1; 120, 7 and 38 kg ha-1; and 99, 6 and 27 kg ha-1 for high, medium and low land rice, respectively. These predicted fertilizer doses increase farmers’ income and protect environment from pollution. Bangladesh Agron. J. 2017, 20(2): 1-9